2015
DOI: 10.18357/ijcyfs.62201513505
|View full text |Cite
|
Sign up to set email alerts
|

How Can Local Governments Level the Social Gradient in Health Among Families With Children? The Case of Norway

Abstract: Abstract:The Norwegian National government has recently developed policies to reduce health inequalities; this should be achieved by a Health in all Policies approach (HIAP). Most policies are to be implemented at the local level and municipalities are responsible for the implementation. The aim of this paper is to answer this question: How can municipalities reduce social inequalities and among families with children through a mixed methods approach, using surveys as well as qualitative interviews in the coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…However, the other types of legitimacy seem to be somewhat more difficult to achieve. Still, all the three municipalities are in the process of legitimising the HiAP approach, supporting earlier research that the implementation of NPHA goals is progressing [30,31].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the other types of legitimacy seem to be somewhat more difficult to achieve. Still, all the three municipalities are in the process of legitimising the HiAP approach, supporting earlier research that the implementation of NPHA goals is progressing [30,31].…”
Section: Discussionsupporting
confidence: 77%
“…However, although the health sector is dominant in many Norwegian municipalities, public health does not represent a defined discipline or profession. There are ongoing debates in the field about its aims, content, priority areas, procedures and ways of working [30,34,12], and public health coordinators and others find this disorientation or complexity challenging [35,36]. Interestingly, we might therefore ask whether the actors promoting HiAP (which might threaten collaborators' professional identities) actually struggle with finding their own professional identities themselves.…”
Section: Discussionmentioning
confidence: 99%
“…They gave little notice to factors outside the domain of the health sector, such as housing, education, youth living conditions, economic circumstances and the labour market. The sectoral focus was still prevalent in 2014 (Fosse & Helgesen, 2015). However, 40 per cent of the municipalities confirmed that living conditions was the main challenge in their health promotion work (Hagen et al, 2016, p. 5), and this was associated with larger municipality size.…”
Section: The New Public Health Act and The Coordination Reformmentioning
confidence: 99%
“…Even these studies showed differences between the municipalities. Some municipalities still prioritised individual lifestyle measures, while others were in the process of integrating the policies across sectors [25]. The findings indicate that there is raised awareness of the significance of social determinants among an increased number of municipalities and that they are in the process of developing policies specifically to level the social gradient in health.…”
Section: Hiap and Social Equity-the "New" Concept Of Public Healthmentioning
confidence: 94%